Beyond the web: integrated digital communities. (26th April 2005) - Sillence, Elizabeth
This paper details two case studies exploring integration within digital communities. Three types of integration are introduced – information, technological and online–offline integration. These concepts are explored through two online fan communities and through a mobile web-based system. All types of integration were present and are vital to the communication and interaction needs of the members.